2020
DOI: 10.20546/ijcmas.2020.911.452
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of Plant Growth Regulators on Growth, Flowering and Xanthophyll Content of African Marigold (Tagetes erecta L.)

Abstract: Production of marigold can be improved to a large extent by the judicious cultural operations i.e. application of optimum fertilizer at required time, crop management practices and use of plant growth regulators. Hence, an experiment was carried out in the Research Farm of Adhiparasakthi Horticultural College, Kalavai, during 2018-19 to find out the effect of plant growth regulators (NAA, GA 3 ) and growth retardants (Maleic hydrazide, Alar) on growth and yield of African marigold var. Pusa Narangi Gainda. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The findings of this study also demonstrated that the addition of Zn and Fe improved plant physiological parameter i.e total chlorophyll content in leaf. Similar results found by earlier workers [6,7,8] and [9].…”
Section: Biochemical Attributessupporting
confidence: 93%
“…The findings of this study also demonstrated that the addition of Zn and Fe improved plant physiological parameter i.e total chlorophyll content in leaf. Similar results found by earlier workers [6,7,8] and [9].…”
Section: Biochemical Attributessupporting
confidence: 93%
“…"The increase in flowering attributes may be due to the beneficial role of micronutrients in enhancing the translocation of carbohydrates, minerals and amino acids from the site of the synthesis to the storage tissue especially on flowers" as reported by Sha and Karuppaiah [2] in chilli, Patil et al [3] in sunflower, Balakrishnan et al [4] in African marigold and Naveen kumar et al [5] in chrysanthemum. Thirumalmurugan et al [6] also reported that a significant increase in the maximum number of flowers was noticed under the treatment (Zinc @ 0.5% + Boron @ 0.5%). The maximum flower diameter was increased with Recommended Dose of Fertilizer +Zn+Mn+B Fe, soil application + Zn EDTA +Mn EDTA + B +Fe EDTA (@ 0.4% each as foliar application) in leaves Swetha et al [7] in gaillardia.…”
Section: Flowering Attributesmentioning
confidence: 89%
“…Similarly, NAA enhance the cell elongation and division by promoting the DNA synthesis in the cell. It reduced the juvenile phase due to increase in Influence of Plant Growth Regulators on Growth, Yield and Yield Components in Garden Pea photosynthesis and respiration with enhanced CO 2 fixation in the plant (Murugan et al, 2020). The another plant growth regulator is salicylic acid (SA) which is considered as a phenolic antioxidant compound, messenger, or signaling molecule and growth regulator which support the plant growth and performance under different stressors.…”
Section: Introductionmentioning
confidence: 99%